2006
DOI: 10.1590/s1806-37132006000500003
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre o manejo da asma em uma unidade de referência da rede pública de Porto Alegre (RS) e as proposições do III Consenso Brasileiro no Manejo da Asma

Abstract: Objective: To determine whether the guidelines put forth in the ΙΙΙ Brazilian Consensus on Asthma Management are being applied in a population of asthma patients treated at a public hospital that is a referral center for asthma in the city of Porto Alegre, Brazil. Methods: All adult asthma patients who began their treatment between 1999 and 2002 were evaluated. The treatment given was classified as consistent or inconsistent with the Consensus guidelines. The clinical features of asthma and the frequency of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…A retrospective study performed in a Brazilian university reported results similar to ours in terms of the mean age, the proportion of women and the proportion of patients with severe asthma among the patients in treatment [16]. Based on the evaluation of the last prescription in the records, the use of the pharmacological treatment in accordance with the guideline recommendations for the asthma management at that time was low.…”
Section: Resultssupporting
confidence: 58%
“…A retrospective study performed in a Brazilian university reported results similar to ours in terms of the mean age, the proportion of women and the proportion of patients with severe asthma among the patients in treatment [16]. Based on the evaluation of the last prescription in the records, the use of the pharmacological treatment in accordance with the guideline recommendations for the asthma management at that time was low.…”
Section: Resultssupporting
confidence: 58%
“…In a study conducted in the city of Porto Alegre, Brazil, ( 23 ) the medical records of patients treated in a pulmonology department were analyzed. Approximately 68% of the patients had received treatment that was not in accordance with the recommendations in current guidelines, and 71% of those patients had uncontrolled asthma that was not being treated with corticosteroids.…”
Section: Discussionmentioning
confidence: 99%